Use of proteinase K for RT-PCR of cytokine mRNA in formalin fixed tissue - Davies, Graham N (1996)
Fresh tissue from cases of sudden infant death syndrome is becoming increasingly scarce and therefore researchers interesting in studying the aetiology of this syndrome have had to resort to archival tissue, usually in the form of paraffin wax sections. A simple method for isolating mRNA from formalin fixed, paraffin wax embedded material of sufficient purity for reverse transcription (RT)-PCR is described. Proteinase K treatment of formalin fixed, wax embedded tissue followed by RNA STAT-60 extraction was successful in isolating mRNA suitable for RT-PCR. Interleukin (IL)-1α, IL-6 and tumour necrosis factor (TNF) transcripts were amplified successfully from heart, but not thyroid, kidney or liver tissue, of a patient who died following rejection of a transplanted heart, and IL-1α, but not IL-6 or TNF, transcripts from lung tissue of a six month old baby who died of viral pneumonia. Transcripts of a housekeeping gene were detected in all tissues. This method should be useful for examining gene expression in archival material.